An efficient ternary catalyst ZnBr2/K2CO3/[Bmim]Br for chemical fixation of CO2 into cyclic carbonates at ambient conditions. (June 2016) - Zhang, Huizi; Kong, Xianqiang; Cao, Changsheng; Pang, Guangsheng; Shi, Yanhui
Graphical abstract: Highlights: A ternary catalytic system of ZnBr2 /K2 CO3 /[Bmim]Br was developed. The catalyst is effective for both internal and terminal epoxides. The catalytic activity do not be affected by little contamination of water and air. This catalyst is reusable for at least 5 times. Abstract: A simple, readily available and recyclable ternary catalytic system of ZnBr2 /K2 CO3 /[Bmim]Br was developed for the efficient conversion of CO2 and epoxides (both internal and terminal epoxides) to cyclic carbonates under very mild conditions (room temperature, 1 atm) with excellent yields (>90% for 18 examples). The catalytic activity would not be affected by CO2 in the presence of small amount of water and air. The reactions would even be carried out under CO2 partial pressure as low as 0.5 atm, giving carbonate in good yield. This process has been repeated 5 times without any obvious decrease in catalytic activity. The influences of the type of catalyst, catalyst loading, CO2 pressure, reaction time, and temperature on the reaction yields have been investigated. The possible reaction mechanism was proposed based on the reaction results.